A population-based study of preeclampsia and eclampsia in Ecuador: ethnic, geographical and altitudes differences - Eduardo Tejera; Maria Eugenia Sánchez; Aquiles R. Henríquez-Trujillo; Yunierkis Pérez-Castillo; Marco Coral-Almeida (BMC Pregnancy and Childbirth, 2021)
Abstract Background In Ecuador eclampsia and preeclampsia were identified as the third cause of maternal death. Like other Latin-American countries, Ecuador has human settlements living from 0 to more than 4000 m of altitude and comprising a wide ethnic-diversity across all these altitude changes. These characteristics offer the possibility to study a wide variety of possible risk factors for preeclampsia and eclampsia. Methods We conducted a population-based retrospective study of all deliveries in Ecuador from 2015 through 2017. The main variables analyzed were: altitude, ethnic self-identification, geographic location, and maternal age. The data comes from the Ecuadorian National Institute of Statistics and Census (INEC) and the Ecuadorian Ministry of Health. Data information regarding maternal parity and socioeconomic status was not available from official records. Logistic regression analysis was used to study the relationship between preeclampsia and eclampsia with the variable of interest. Geospatial statistical analysis was done to identify statistically significant spatial clusters of preeclampsia and eclampsia cases. Results The incidence of preeclampsia was estimated between 5.11 (5.05–5.18) and 6.23 (6.16–6.30), and 0.25 (0.23–0.26) for eclampsia. Native American have a lower incidence regarding preeclampsia compared to other ethnic groups. High altitude has a significant odds ratio (OR = 2.31, 1.93–2.78) of preeclampsia. Montubio residing in middle altitude (1500–3500 m) have the highest risk of preeclampsia (OR = 18.13, 9.53–34.50). Afro-Ecuadorians also have an increased risk of preeclampsia associated with altitude (OR = 2.36, 1.78–3.14). Ethnicity was not identified as a risk factor for eclampsia. Early and older maternal age was associated with an increased risk of preeclampsia and eclampsia. Women living more than 20 km from the obstetric unit have an OR = 2.61 (2.32–2.95, p-value< 0.01) and OR = 1.87 (1.82–1.92, p-value< 0.01) of developing eclampsia and preeclampsia respectively. Conclusions Preeclampsia is widespread across low and high-altitude areas, while eclampsia is mostly located at lower altitudes. Montubios living at middle or high altitudes represents the ethnic group with a higher risk of preeclampsia. No ethnic effect was identified as a potential risk factor for eclampsia. Moreover, in eclampsia the associated risk of young women seems to be higher than in preeclampsia.